1999
DOI: 10.3727/036012999816356372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Peripheral T Lymphocyte Subpopulation and Amounts of Cerebral Catecholamines in Mice

Abstract: The aim of this study was to investigate the effects of acupuncture on peripheral lymphocyte subpopulations and cerebral catecholamines. In order to examine the effects of acupuncture, two experiments were performed. Experiment 1: Eighteen female mice (strain; C57BL/6) at the age of 7 weeks were divided three groups, (a) sham operated (control; n=6), (b) ovariectomized (OVX; n=6), and (c) ovariectomized and stimulated by subcutaneous needles on acupuncture point, Shenshu (BL23) at the both sides of the back fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Gao et al (1997) found that EAC of Tsu-San-Li significantly increased the -receptor binding sites in the striatum, septal nucleus, and amygdaloid nucleus but not in the nucleus accumbens and dorsal raphe nucleus. This agrees with the finding that EAC stimulates dopaminergic turnover (Okumura et al, 1999). It has been shown that EAC can cause the release of endogenous opioids to activate specific receptors, especially to increase -receptor binding sites (Chen and Han, 1992).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gao et al (1997) found that EAC of Tsu-San-Li significantly increased the -receptor binding sites in the striatum, septal nucleus, and amygdaloid nucleus but not in the nucleus accumbens and dorsal raphe nucleus. This agrees with the finding that EAC stimulates dopaminergic turnover (Okumura et al, 1999). It has been shown that EAC can cause the release of endogenous opioids to activate specific receptors, especially to increase -receptor binding sites (Chen and Han, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…A frequency of 1 to 100 Hz, as used in the present study, is applied with animal models for rats, rabbits, and mice (Chang et al, 1995a(Chang et al, , 1996Okumura et al, 1999). The same procedures were carried out twice a week for 1 or 3 consecutive weeks.…”
Section: Electroacupuncturementioning
confidence: 99%
“…In both human and animal models, flow cytometry reveals that acupuncture reduces levels of CD4+ and CD8+ cells, which are known to suppress overactive immune response and to increase cytotoxic NK cell activity [28,29]. One study of reaction to immuneand non-immune-related acupuncture points revealed not only T-cell modulation, but also an increase of soluble interleukin-2 receptor, and a decrease of cytokines interleukin-4 and interleukin-6.…”
Section: Immunomodulationmentioning
confidence: 98%
“…16 Previous studies showed that surgical trauma suppressed T lymphocyte proliferation and EA administration restored suppressed lymphocyte proliferation. 17 Cheng et al 18 noted that EA at ST36 acupuncture point might increase lymphocyte proliferation of surgically traumatised rats. 8 These results also suggested that acupuncture might improve immunosuppression after surgical trauma.…”
Section: Discussionmentioning
confidence: 99%